2009
DOI: 10.1167/iovs.08-2489
|View full text |Cite
|
Sign up to set email alerts
|

SPARC-null Mice Exhibit Lower Intraocular Pressures

Abstract: SPARC-null mice have lower IOPs than do their WT counterparts with equal CCTs. The rate of aqueous turnover suggests that the mechanism is enhanced outflow resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 45 publications
(42 reference statements)
7
93
0
Order By: Relevance
“…However, differences in collagen composition of the sclera may be correlated with suboptimal optic nerve head biomechanics, resulting in increased susceptibility to axonal damage in glaucomatous eyes. 66,67 The extracellular composition of the sclera is influenced and modified as a result of intraocular pressure fluctuations 68 and PACG-associated variants have also 73 Cong et al, 69 Wang et al, 70 Micheal 109 Chua et al, 104 Haddadin et al 110 …”
Section: Pacg Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, differences in collagen composition of the sclera may be correlated with suboptimal optic nerve head biomechanics, resulting in increased susceptibility to axonal damage in glaucomatous eyes. 66,67 The extracellular composition of the sclera is influenced and modified as a result of intraocular pressure fluctuations 68 and PACG-associated variants have also 73 Cong et al, 69 Wang et al, 70 Micheal 109 Chua et al, 104 Haddadin et al 110 …”
Section: Pacg Risk Factorsmentioning
confidence: 99%
“…108,109 SPARC-null mice reportedly display lower IOP than wild-type animals, which suggests a potential role for SPARC in regulating IOP. 110 Furthermore, investigation of two patient cohorts of Southern Chinese origin with acute and chronic PACG has led to the identification of an association between CALCRL polymorphisms and acute but not chronic PACG. 111 CALCRL (calcitonin receptor like) and related receptors are a family of G-protein-coupled receptors that comprise several subtypes.…”
Section: Nebmentioning
confidence: 99%
“…Intraocular pressures were recorded in both eyes of each animal with a handheld commercial rebound tonometer according to instructions by the manufacturer (TonoLab, Icare, Espoo, Finland). All measurements were taken between 4 and 7 min after anesthetic injection, as suggested by a prior study (20); 5 to 10 measurements of IOP in each eye were taken and the mean value of the IOP of the left operated eye is expressed as a percentage over that of the unoperated right eye of the same animal. An IOP that is < 70% of baseline IOP is used as an indicator of effective filtration and bleb function.…”
Section: Measurement Of Iopmentioning
confidence: 99%
“…Other groups have measured IOP in genetically modified mice lacking specific ECM molecules. This approach has identified SPARC, and thrombospondins-1 and -2 as having key roles in IOP regulation [19,20]. Perfusion of versican RNAi silencing lentivirus, or a recombinant HepII domain of fibronectin, has also implicated versican and fibronectin [48,57,58].…”
Section: Regulation Of Aqueous Humor Outflow Resistancementioning
confidence: 99%
“…These particular matricellular proteins are also expressed in the JCT of the TM and their function in IOP regulation is just beginning to be realized. Measurement of IOPs in these knockout mice has shown that genetic ablation of some matricellular genes exhibit lower IOPs (TSP-1, TSP-2, SPARC) [19,20], while for others there is no significant effect on IOP (hevin, osteopontin, tenascin C, tenascin X) [21,22,32]. What one will notice is that there seems to be an intriguing commonality between these groups of molecules and the two biological processes ( Table 1): molecules that do not contribute to IOP regulation are ones that are expressed during the inflammatory phase of the FBR (hevin, OPN), while ablation of molecules that affect IOP are those that are involved in capsule formation during the FBR (SPARC, TSP-1, TSP-2).…”
mentioning
confidence: 99%